After the Peasants’ War: Barbara (Schweikart) von Fuchstein Fights for Her Property - Ocker, Christopher (Renaissance and Reformation / Renaissance et Réforme, 2017)
Historians are only beginning to appreciate fully the political and social impact of the aftermath of the German Peasants’ War. The case of Barbara (Schweikart) von Fuchstein, widow of Sebastian von Fuchstein, a Kaufbeuren lawyer suspected of Anabaptism and exiled at the end of the war, sheds light on the role of middle-rank nobility in the process of post-war reordering. Her eventual success in a conflict with her violent cousin, Ulrich Schweikert, a knight in the service of the Abbot of Kempten, draws attention to middle-rank competition in the Upper Allgäu, where historians have emphasized the tenacity of peasants and the long-term winnings of princes. Her case also illustrates the flux of religious identities at ground level in the early Reformation, among lay people whose interest in the religious controversy was secondary to, perhaps inseparable from, family business.